PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELOMPOK XI IPS SMA NEGERI 1 HARAU - Latifah Umaiyah Z (Jurnal Edukasi dan Penelitian Matematika, 2022)
Mathematical concepts Understanding  is one of the basic abilities that are expected to be possessed by every student in learning mathematics. Based on observations made in class XI of SMA Negeri 1 Harau, it is known that students continue to have poor understanding of mathematical concepts. One of the ways to get past a challenge the problems above is to apply the Think Pair Share (TPS) cooperative learning model in the mathematics learning process. The study purpose was to reveal, analyze and describe whether the understanding of the mathematical concepts of students who studied using the TPS Type Model of Cooperative Learning was better than the understanding of the concepts of students who learned to use the direct learning model. This research type was a quasi-experimental with a nonequivalent posttest research design. -only control group design. Based on the analysis of the mathematical concept understanding test data, it was obtained that understanding of the concepts of students who use the TPS learning model is better than the understanding of the concepts of students who learn with the direct learning model. So it can be said that there is an influence of the TPS learning model on the understanding of students' mathematical concepts.Keywords– TPS, Understanding Mathematical Concepts.